Wie Siedlungsentwicklung steuern? Fallstudien zur Regionalplanung und Wohnungsbauförderung in Nordrhein-Westfalen - Droß, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Because of the finance problems of the civil sector and the needs of securing the services of public interest we need a consequent control of settlement development. But are the required instruments available? This paper focuses on the regional planning and the housing support. Their contribution to the control of the housing settlement development is analysed by case studies in North Rhine-Westphalia. The intention of the paper is to find ways for improving the control of the settlement development.